Mechanical quantum sensing in the search for dark matter. (18th January 2021) - Carney, D; Krnjaic, G; Moore, D C; Regal, C A; Afek, G; Bhave, S; Brubaker, B; Corbitt, T; Cripe, J; Crisosto, N; Geraci, A; Ghosh, S; et al.
Abstract: Numerous astrophysical and cosmological observations are best explained by the existence of dark matter, a mass density which interacts only very weakly with visible, baryonic matter. Searching for the extremely weak signals produced by this dark matter strongly motivate the development of new, ultra-sensitive detector technologies. Paradigmatic advances in the control and readout of massive mechanical systems, in both the classical and quantum regimes, have enabled unprecedented levels of sensitivity. In this white paper, we outline recent ideas in the potential use of a range of solid-state mechanical sensing technologies to aid in the search for dark matter in a number of energy scales and with a variety of coupling mechanisms.